The Problems of Punishing People Smuggling Perpetrators as a Transnational Organized Crime Network - Siahaan, Herbin Marulak; Saragih, Jogi Talar (Jurnal Penegakan Hukum dan Keadilan, 2025)
Due to its status as the largest archipelagic nation globally, Indonesia is very susceptible to transnational organized crime, particularly offenses related to smuggling people. To address this issue, the country changed Law Number 9 of 1992 regarding immigration and enacted Law Number 6 of 2011, which makes people smuggling a criminal offense to comply with the United Nations Protocol Against the Smuggling of Migrants by Land, Sea, and Air in 2000, which it had ratified. This study seeks to analyze and contrast law enforcement methods in cases of people smuggling, both prior to and following the enactment of Law No. 6 of 2011. This research employed a doctrinal methodology that falls within the qualitative legal research category. The findings indicate that there is no substantial disparity in law enforcement procedures before and during the implementation of Law No. 6 of 2011. Law enforcement officials encounter difficulties in collecting the necessary evidence to establish crucial aspects of people’s smuggling, such as the pursuit of financial gain by the perpetrator network. The new immigration law has not yet enabled law enforcement against people smugglers to be more effective.